The function and effect on prognosis of ANXA2 in gastric cancer peritoneal metastasis patients in cold region - Jin Shiyang; Liang Longxu; Huang Xiaoyi; Wang Kuan (Frigid Zone Medicine)
Heilongjiang Province is part of the northern cold areas of China, where gastric cancer is one of the most common gastrointestinal malignancies. Peritoneal metastases (PM) are the leading cause of mortality among patients. This study conducted bioinformatics and basic research on the gene ANXA2 (Annexin A2), which may influence the prognosis of patients.